Tinjauan Yuridis Tindak Pidana Peredaran Narkotika Jenis Shabu Studi Putusan “731/Pid.Sus/2022/PN.Mks” - Andi Rahma; Andi Zulkarnain; Ernalia Rahayu (Pledoi Law Jurnal, 2023)
ABSTRACT: The purpose of this research is to determine the application of criminal law regarding the distribution of the drug known as shabu, in order to understand the judge's law in imposing criminal sanctions on the perpetrator of the distribution of the drug known as shabu in the case